Interpretation Acts—Are They, and (How) Do They Make for, Great Law?. (28th April 2021) - Carter, Ross
Abstract: The paper considers the purposes and evolution of Interpretation Acts, including the following points:  how, as default law, they inform and interact with other legislation;  their scope as, and interaction with other, interpretation law (including links with interpretation legislation in related jurisdictions);  ways they can stop being, or fail to be, great law (that is, law that is accessible, fit for purpose, and constitutionally sound);  ways policy-makers and drafters can meet the challenges (in Te Reo Māori: ngā wero) of making them, and all the other law that interacts with them, great law.